Sobrecarga de trabalho de enfermeiros em unidades de internação hospitalar - Trindade, Liliane Ribeiro (2018)
The present study had as general objective to know the perception of nurses who work in shift work on work overload. This is a qualitative research, exploratory-descriptive type. The scenario was a university hospital located in a municipality in the interior of the State of Rio Grande do Sul, Brazil. The participants were the nurses working in the clinical and surgical hospitalization units of this institution. The technique of data collection was performed through non - participant systematic observation and semi - structured interview, and were analyzed through the thematic content analysis technique. Inclusion criteria were: to work in the units studied more than six months ago. The recommendations set forth in Resolution 466/2012 of the National Health Council were followed, respecting the regulatory norms of research involving human beings, with approval under the number CAAE 65329817.2.0000.5346. From the analysis of the data emerged the categories: Factors inherent to the nurses' work process, which dealt with the reduced number of professionals in the work environment, interruptions in the development of activities, influence of the work shifts and the demands of a hospital school; Factors that interfere in the workload of nurses, in which adverse situations were discussed in the work environment, activities besides the capacity for resolution, changes in the epidemiological profile of the population, and managerial activities and the extension of work at home; and Elements that collaborate for the development of the work, in which the use of technologies in the development of work, recognition and valorization of the profession were portrayed. It is concluded that the nurses who work in shifts perceive the work overload, which is related to the accumulation of functions, of different complexities, which may or may not be the nurse's competence, and which need to be performed in the shortest possible time, without compromising the quality of care. It is necessary to develop strategies regarding the preservation of the health of workers, providing that nursing is more valued, and supported by the health team, making possible the provision of integral quality assistance.